Spectrophotometric ˗Indirect Method for Chlordiazepoxide Estimation in Dosage Forms via Charge˗Transfer Complex Formation with Metol - Hadi, Hind; Jamal, Mariam (Jordan Journal of Pharmaceutical Sciences, 2020)
Aims: An accurate, simple, and reliable spectrophotometric indirect method for chlordiazepoxide (CDE) determination in its pure and pharmaceutical dosage forms is demonstrated.Methods: The method is based on the formation of charge˗ transfer complex between decomposed CDE and Metol (N-methyl-p-aminophenol sulfate) in the presence of potassium dichromate to produce an intense red complex that is stable and have a maximum absorbance at 516 nm.Results: The calibration curve shows that Beer’s law is obeyed in the concentration range of 3−60 µg/mL, with a correlation coefficient of 0.9994, and a molar absorptivity of 3.24×103 L/mol cm. All the variables that affected on the sensitivity and stability of the formed product were studied and optimized Conclusion: The suggested method was applied successfully for CDE determination in pharmaceutical dosage forms.